Clinical and Autoimmune Characteristics of Severe and Critical Cases of COVID‐19. Issue 6 (14th May 2020) - Zhou, Yaqing; Han, Tao; Chen, Jiaxin; Hou, Can; Hua, Lei; He, Shu; Guo, Yi; Zhang, Sheng; Wang, Yanjun; Yuan, Jinxia; Zhao, Chenhui; Zhang, Jing; et al.
Abstract : In this study we report on the clinical and autoimmune characteristics of severe and critical novel coronavirus pneumonia caused by severe acute respiratory syndrome‒associated coronavirus 2 (SARS‐CoV‐2). The clinical, autoimmune, and laboratory characteristics of 21 patients who had laboratory‐confirmed severe and critical cases of coronavirus disease 2019 (COVID‐19) from the intensive care unit of the Huangshi Central Hospital, Hubei Province, China, were investigated. A total of 21 patients (13 men and 8 women), including 8 (38.1%) severe cases and 13 (61.9%) critical cases, were enrolled. Cough (90.5%) and fever (81.0%) were the dominant symptoms, and most patients (76.2%) had at least one coexisting disorder on admission. The most common characteristics on chest computed tomography were ground‐glass opacity (100%) and bilateral patchy shadowing (76.2%). The most common findings on laboratory measurement were lymphocytopenia (85.7%) and elevated levels of C‐reactive protein (94.7%) and interleukin‐6 (89.5%). The prevalence of anti‒52 kDa SSA/Ro antibody, anti‒60 kDa SSA/Ro antibody, and antinuclear antibody was 20%, 25%, and 50%, respectively. We also retrospectively analyzed the clinical and laboratory data from 21 severe and critical cases of COVID‐19. Autoimmune phenomena exist in COVID‐19 subjects, and the present results provide the rationale for a strategy of preventing immune dysfunction and optimal immunosuppressive therapy.